Survey of energy-related occupant perceptions in a green-rated and in a non-rated building. Issue 1 (2nd January 2022) - Almeida, Laura M. M. C. E.; Tam, Vivian W. Y.; Le, Khoa N.; Huang, Zhiyu; Forbes, Samuel
ABSTRACT: Surveys were delivered to the occupants of two university buildings in Sydney Australia to collect occupant perceptions related with energy use and the impact of the 'green' rating in occupant behaviour. Overall, 100 surveys were delivered in a 6-star building, rated according to the certification system Green Star, and in a non-rated building, from Western Sydney University. Occupants were inquired about their perception and interactions with heating, cooling, lighting, windows/doors opening, windows blinds and plug loads. This made possible to understand if there is a significant difference in energy-related occupant behaviour when comparing a green-rated to a non-green-rated building. Additionally, this study analysed if occupant's gender, age and work role, as well as the characteristics of the built environment have impact on occupant behaviours and actions. It was possible to conclude that the 'green' rating has no impact in the way occupants interact with the buildings' systems, and variables such as gender, age and the characteristics of the built environment have impact in the way occupants interact with the building features and systems. The results were obtained according to statistical analysis and intend to be a guideline for future research in the field of energy-related occupant behaviour.